Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.17576/3l-2020-2602-04
|View full text |Cite
|
Sign up to set email alerts
|

Power and Voices of Authority in the Media Narrative of Malaysian Natives: Combining Corpus Linguistics and Discourse Analysis Approaches

Abstract: Orang Asli is a group of indigenous people who live according to a set of lifestyle and belief system and speak the native language. Previous studies have found that the Orang Asli are mostly depicted in the news media as backwards and dependent on others (Marlina Jamal & Shakila Abdul Manan, 2016). Such stereotypical depiction is shared with other research undertaken in various countries, particularly those in Canada or Australia. While many of these studies analysed findings from the media and communication … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 15 publications
(26 reference statements)
0
0
0
Order By: Relevance
“…Tinjauan teoritis digunakan untuk menganalisis dan mengkaji berbagai konsep, teori, literatur,atau penelitian yang terkait dengan suatu topik tertentu. Dalam penelitian ini, tinjauan teoritis terdiridari tiga penelitian sejenis, yang pertama penelitian yang dilakukan oleh (Ismail et al 2020) dengan judul Power and Voices of Authority in the Media Narrative of Malaysian Natives: Combining Corpus Linguistics and Discourse Analysis Approaches. Hasil penelitian ini menunjukan bahwa istilah "Orang Asli" secara konsisten digambarkan di sekitar narasi berita stereotip seperti isu hak atas tanah dan sumber daya lainnya.…”
Section: Tinjauan Literaturunclassified
“…Tinjauan teoritis digunakan untuk menganalisis dan mengkaji berbagai konsep, teori, literatur,atau penelitian yang terkait dengan suatu topik tertentu. Dalam penelitian ini, tinjauan teoritis terdiridari tiga penelitian sejenis, yang pertama penelitian yang dilakukan oleh (Ismail et al 2020) dengan judul Power and Voices of Authority in the Media Narrative of Malaysian Natives: Combining Corpus Linguistics and Discourse Analysis Approaches. Hasil penelitian ini menunjukan bahwa istilah "Orang Asli" secara konsisten digambarkan di sekitar narasi berita stereotip seperti isu hak atas tanah dan sumber daya lainnya.…”
Section: Tinjauan Literaturunclassified
“…Much of the literature has revolved around the historical background, sociopolitical, socioeconomic, and more recently the contemporary issues surrounding the Orang Asli such as social issues concerning their land rights, health, and education. Thus far, studies which have examined the representation of the Orang Asli in the media have revealed that the community does not enjoy a fair and balanced portrayal by the mainstream media and is consistently represented in a stereotypical and demeaning manner [4,16,17,18,19,36,37]. Despite the findings, both journalists and JAKOA themselves have strongly refuted the claim that the Orang Asli are represented in such a manner [36].…”
Section: Past Studiesmentioning
confidence: 99%
“…Different methodological approaches have been utilised to examine the representation of the Orang Asli whereby earlier studies opted for a content analysis approach [16, 34(37)] whereas newer studies utilised different discourse analytical approaches [4,17,18,19,32]. [18]'s study was the first study to adopt a CDA approach by using a combination of van Dijk's (1980) Theory of Semantic Macrostructures and van Dijk's (1998) Theory of Ideology in examining the macro and microstructures of the news reports from The Star in deconstructing the ideological representation of the Orang Asli.…”
Section: Past Studiesmentioning
confidence: 99%
See 2 more Smart Citations